Factors associated with influenza vaccine uptake among healthcare workers in Georgia, 2021–2024 - Oksana Artemchuk; Giorgi Chakhunashvili; Iris Finci; Madelyn Rojas; Esther Kissling; Khatuna Zakhashvili; Mark A. Katz; Lia Sanodze (PLOS One, 2026)
Background Healthcare workers (HCWs) are prioritised to receive influenza vaccine annually in Georgia. We aimed to identify factors associated with influenza vaccine uptake among Georgian HCWs. Methods We used self-reported influenza vaccination data for three influenza seasons (2021–2024) and 2023 survey data on attitudes towards influenza from a prospective cohort of HCWs in six hospitals in Georgia. HCWs who received influenza vaccine in at least one season were compared with those who were not vaccinated in any season. Adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were calculated using multivariable logistic regression to identify factors associated with vaccination uptake. Findings Of 403 participants, the median age was 46 (IQR 36–54), 364 (90%) were female, 168 (42%) were nurses or midwives, 85 (21%) were support staff, 75 (19%) were doctors, and 75 (19%) were other staff. Overall, 289 (72%) received influenza vaccine in at least one season, while 114 (28%) did not receive it in any season. Multivariable analysis showed no differences in vaccine uptake by sex or occupation. HCWs ≥ 30 years were more likely to be vaccinated, with those aged 40–49 having the highest odds (aOR 2.67, 95% CI 1.09–6.59). HCWs who did not believe the vaccine was safe (aOR 0.27, 95% CI 0.11–0.68), those who doubted its effectiveness (aOR 0.36, 95% CI 0.14–0.89), and HCWs at Hospital B (aOR 0.06, 95% CI 0.02–0.23) were less likely to be vaccinated. Conclusions Georgian HCWs who questioned influenza vaccine safety and effectiveness, and those at one hospital, had lower odds of vaccination over three years, whereas older HCWs were more likely to be vaccinated. Future campaigns to promote influenza vaccination among HCWs should address safety and effectiveness concerns and target demographic disparities.